Kids Nowadays Hear Better Than We Did: Declining Prevalence of Hearing Loss in US Youth, 1966–2010. (5th October 2018) - Hoffman, Howard J.; Dobie, Robert A.; Losonczy, Katalin G.; Themann, Christa L.; Flamme, Gregory A.
Abstract : Objectives/Hypothesis: To investigate factors associated with hearing impairment (HI) in adolescent youths during the period 1966–2010. Study Design: Cross‐sectional analyses of US sociodemographic, health, and audiometric data spanning 5 decades. Methods: Subjects were youths aged 12 to 17 years who participated in the National Health Examination Survey (NHES Cycle 3, 1966–1970; n = 6, 768) and youths aged 12 to 19 years in the Third National Health and Nutrition Examination Survey (NHANES III, 1988–1994; n = 3, 057) and NHANES (2005–2010; n = 4, 374). HI prevalence was defined by pure‐tone average (PTA) ≥ 20 dB HL for speech frequencies (0.5, 1, 2, and 4 kHz) and high frequencies (3, 4, and 6 kHz). Multivariable logistic models were used to estimate the odds ratio (OR) and 95% confidence interval (CI). Results: Overall speech‐frequency HI prevalence was 10.6% (95% CI: 9.7%‐11.6%) in NHES, 3.9% (95% CI: 2.8%‐5.5%) in NHANES III, and 4.5% (95% CI: 3.7%–5.4%) in NHANES 2005 to 2010. The corresponding high‐frequency HI prevalences were 32.8% (95% CI: 30.8%‐34.9%), 7.3% (95% CI: 5.9%‐9.0%), and 7.9% (95% CI: 6.8%‐9.2%). After adjusting for sociodemographic factors, overall high‐frequency HI was increased twofold for males and cigarette smoking. Other significant risk factors in NHANES 2005 to 2010 included very low birth weight, history of ear infections/otitis media, ear tubes, fair/poor general health, and firearms use. Conclusions: HI declined considerably between 1966 to 1970 and 1988 to 1994, with no additional decline between 1988 to 1994 and 2005 to 2010. Otitis media history was a significant HI risk factor each period, whereas very low birth weight emerged as an important risk factor after survival chances improved. Reductions in smoking, job‐related noise, and firearms use may partially explain the reduction in high‐frequency HI. Loud music exposure may have increased, but does not account for HI differences. Level of Evidence: NA Laryngoscope, 129:1922–1939, 2019